Structure optimization of jacquard lifting knife on NURBS curve - YANG ZhenNing; LI YuLiang (Jixie qiangdu)
In view of the problem that large jacquard machine was prone to bending deformation when bearing load, resulting in insufficient lifting height of lifting knife, so that the straight needle hook can not be caught by the electromagnetic device. Firstly, the structure, load and movement of crank slider driving mechanism were analyzed. Secondly, based on the theory of variable cross-section beam and the method of structure optimization, non uniform rational B-splines (NURBS) method was used to express the side and cross-section shape of the lifting knife. Inertia moment function and bending moment function of the lifting knife cross-section were calculated by numerical method, and deflection of the lifting knife was calculated by finite difference method. The deflection calculation method in this paper was verified by the finite element method (FEM) and equivalent beam method with an error of less than 10%. Finally, aiming at the minimum quality, the primal-dual infeasible-interior-point algorithm was used to optimize the lifting knife structure. The optimization result shows that compared with the optimized initial value model, the mass of lifting knife decreases by about 1.7% and the maximum deflection decreases by about 26.67%.